Noncanonical Wnt5a Signaling Suppresses Hippo/TAZ-Mediated Osteogenesis Partly Through the Canonical Wnt Pathway in SCAPs - Fu Y; Ma D; Fan F; Sun T; Han R; Yang Y; Zhang J (Dove Medical Press, 2022)
Yajing Fu,1 Dan Ma,2 Fengyan Fan,3 Tongke Sun,1 Ruiqi Han,1 Yanran Yang,1 Jun Zhang1 1Shandong University & Shandong Key Laboratory of Oral Tissue Regeneration & Shandong Engineering Laboratory for Dental Materials and Oral Tissue Regeneration, Department of Orthodontics, School and Hospital of Stomatology, Cheeloo College of Medicine, Shandong University, Jinan, People's Republic of China; 2Department of Orthodontics, Shandong Provincial Hospital Affiliated to Shandong First Medical University, Jinan, People's Republic of China; 3Department of Orthodontics, Hangzhou Stomatological Hospital, Hangzhou, People's Republic of ChinaCorrespondence: Jun Zhang, Shandong University & Shandong Key Laboratory of Oral Tissue Regeneration & Shandong Engineering Laboratory for Dental Materials and Oral Tissue Regeneration, Department of Orthodontics, School and Hospital of Stomatology, Cheeloo College of Medicine, Shandong University, No. 44-1 Wenhua Road West, Jinan, People's Republic of China, Tel +86 139 5310 9816, Email zhangj@sdu.edu.cnPurpose: Stem cells from the apical papilla (SCAPs) are promising seed cells for tissue regeneration medicine and possess the osteogenic differentiation potential. Wnt5a, a typical ligand of the noncanonical Wnt pathway, exhibits diverse roles in the regulation of osteogenesis. The transcriptional co-activator with PDZ-binding motif (TAZ, WWTR1) is a core regulator in the Hippo pathway and regulates stem behavior including osteogenic differentiation. This study aims to examine how Wnt5a regulates SCAPs osteogenesis and explore the precise mechanistic relationship between Wnt5a and TAZ.Methods: SCAPs were isolated from developing apical papilla tissue of extracted human immature third molars in vitro. ALP staining, ALP activity and Alizarin red staining were used to evaluate osteogenic capacity. Osteogenic-related factors were assessed by qRT-PCR or Western blotting. Additionally, the receptor tyrosine kinase-like orphan receptor 2 (ROR2) was detected by immunocytofluorescence staining and silenced by small interfering RNA to verify the function of Wnt5a/ROR2 in TAZ-mediated osteogenesis. And we constructed TAZ-overexpression and β-catenin-overexpression SCAPs generated by lentivirus to explore the precise mechanistic relationship between Wnt5a and TAZ.Results: Wnt5a (100ng/mL) significantly suppressed ALP activity, mineralization nodules formation, expression of osteogenic-related factors. Meanwhile, it decreased the expression of TAZ mRNA and protein. TAZ overexpression promoted osteogenesis of SCAPs while Wnt5a could block TAZ-mediated osteogenesis. Furthermore, ROR2 siRNA (siROR2) was found to upregulate TAZ and canonical Wnt pathway signaling related molecules such as β-catenin, GSK3β and p-GSK3β. The suppression of Wnt5a/ROR2 on osteogenesis was significantly reversed by β-catenin overexpression through Wnt5a/ROR2/β-catenin/TAZ pathway.Conclusion: Taken together, the present study demonstrates that Wnt5a suppresses TAZ-mediated osteogenesis of SCAPs and there may be a Wnt5a/ROR2/β-catenin/TAZ pathway regulating osteogenesis of SCAPs. Moreover, Wnt5a could be a candidate for regulators in tissue regeneration.Graphical Abstarct: Keywords: Wnt5a, TAZ, stem cells from the apical papilla, osteogenesis, β-catenin